Perspectives of Multicultural Counseling in Elementary School Educatio - Yuliani, Wiwin; Banjarnahor, Nurmauli (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
Counseling is a process to help individuals overcome obstacles to their own development and achieve optimal development of their personal abilities. Given that the people being assisted come from different cultural backgrounds, a deep understanding of counseling services is required. Multicultural counseling, also known as cross-cultural counseling, is a form of counseling to understand clients with different background characteristics. The type of research used by researchers in this research is library research or library research. In carrying out educational activities, multicultural education must also be taught in classrooms, schools and to build students'' and teachers'' critical awareness of what is happening at the moment. The main goal of multicultural education is to make the younger generation become agents to reduce inter-group conflicts (SARA), which usually involve radicalism movements that often occur in Indonesia. Being able to be a role model who is able to accept differences with full tolerance makes the teacher''s task as an educator, this must be balanced with a holistic understanding of multicultural concepts. The attitude that must be changed or improved is that what is must be changed to universalism, with the hope of giving birth to a generation ready to live in tolerance (tasamuh) and multiculturalism, so that there is no exclusive attitude which can make students extreme towards their understanding and less able to have a sense of tolerance and differences between other students (Nugraha, Agung, 2018).